The Collateral Policy of Central Banks - An Analysis Focusing on the Eurosystem - Christopher Weber (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2016)
This dissertation was written by Christopher Weber during his time as a research assistant at the Center for Economic Studies (CES) at the Ludwig-Maximilians-Universität (LMU) Munich. It was handed in at the department of Economics at the LMU Munich in July 2016. The goal of the thesis is to establish the configuration of collateral policy as a tool of central bank policies in pursuit of different objectives, and to present collateral policies in practice, as well as impact and effects of collateral policy. The thesis consists of three parts and nine chapters. The first part discusses the role of collateral in central bank policy. Possible tasks and objectives of central banks are historically deduced in order to then integrate the configuration of collateral policy into the system of objectives. Collateral policy emerges as of relevance towards all central bank objectives. As a result, a normative framework for the role of collateral policy is developed. In the second part, practical collateral policy measures are presented along the lines of this framework. The focus is on the collateral policy of the Eurosystem, which is presented in detail. It has been intensified with respect to several central bank objectives throughout the financial and the European debt crisis. A comparison is made to historical collateral policy measures, as well as the configuration of the collateral frameworks at the Fed, the Bank of England and the Bank of Japan during the recent crisis years. The third part starts with a theoretical foundation of the impact and transmission process of collateral policy within the system of objectives of a central bank. Collateral policy is therefore differentiated into haircut policy and quantity policy and contrasted to classical interest rate policy. The optimal collateral policy with respect to distinct central bank objectives is derived.
Keywords: E50; E61; E63; F33; F36; F45; G01; H12; 330; collateral policy; collateral framework; central bank policy; central bank objectives; Eurosystem; Federal Reserve System; Bank of England; Bank of Japan; European Monetary Union; Eligible Asset Database; reverse transaction; haircut; segmental pooling; rating agency; collateral quality; distribution effects.; Zentralbank; Quantitative Lockerung; Kreditsicherung; Kreditpolitik; Geldpolitik; Schuldenkrise; Wirkungsanalyse; Eurozone; Finanzkrise; Welt